Utilization of dual contraception method among reproductive age women on antiretroviral therapy in selected public hospitals of Northern Ethiopia - Solomon Weldemariam Gebrehiwot; Gedion Asnake Azeze; Carmen C. Robles; Yohannes Mehretie Adinew (BMC, 2017)
Abstract Background Sexually transmitted infections are highly prevalent among pregnant women in Africa. Among the incidence of HIV infection in children, 90% of the infection is attributable to their mothers. Ethiopia is one of the countries with an increasing risky sexual behavior and the most affected by the HIV epidemic. If prevention of mother to child transmission focuses on increasing contraception, it will prevent more than 29% of HIV infection at birth. Therefore, the aim of this study was to assess utilization of dual contraceptive  method and associated factors among reproductive age women on antiretroviral therapy in selected public hospitals of Mekelle town, Northern Ethiopia. Methods Institution based cross-sectional survey was conducted in selected public hospitals of Mekelle among women under antiretroviral therapy from March 1-April 31, 2016. We used a systematic sampling technique to select 331 women. A pretested interviewer administered questionnaire was used for data collection. The data were entered in to Epi data version 3.1 and exported to SPSS version 20 for analysis. Bivariate and multivariable logistic regression analysis was computed. Odds ratio along with 95% CI was computed to ascertain the association. Statistical tests at p-value of < 0.05 were considered as cut off point to determine statistical significance. Results Only 51(15.7%) of participants have utilized dual contraception method. Being single[AOR 5.43, 95% CI (1.61, 18.32)] and cohabitated [AOR 6.06; 95% CI: (2.16, 16.95)] in marital status, having HIV negative partner [AOR 4.44; 95% CI: (1.23, 16.04)], exposure to post diagnosis counseling [AOR 3.03; 95% CI: 1.34, 6.80], disclosed HIV status [AOR 6.06; 95% CI: (1.78, 20.87)] and discussing safer sex with partner [AOR 6.96; 95% CI: (2.75, 16.62)] were positively associated with utilization of dual contraceptive method. Conclusion The overall magnitude of dual contraceptive use is still low in this study. This will be a great concern on the transmission of the virus from mother to babies and partners and risk of complications following unintended pregnancy. This will continue to present as major public health problems in the region unless future interventions focuses on the barriers through tailored counseling and husband involvement in all aspects of the HIV/AIDS care.